ICT and competences (I) (Journal of Parents and Teachers, 2014)
This article talks about IT’s (Information technology), its relationship with the Basic competencies. In this particular article, the author talks about the linguistic communication competency. It focuses on the dimensions and subdimensions in which this competency is organised: oral communication and written communication.
Keywords: new technologies; basic competencies; IT’s; linguistic communication competency.